Dedalo Vola project: The effect of choral singing on physiological and psychosocial measures. An Italian pilot study - Erica Viola; Marco Martorana; Chiara Airoldi; Silvia Caristia; Daniele Ceriotti; Marta De Vito; Riccardo Tucci; Cristina Meini; Giorgio Guiot; Fabrizio Faggiano (Acta Psychologica, 2024)
Several studies have been conducted that show the crucial role of active participation in music in health promotion (e.g. Dingle et al., 2021; Sheppard & Broughton, 2020); however, little research has focused on the biopsychosocial effects of choral singing. The present study aims to evaluate the effectiveness, in terms of improving physiological and psychosocial factors, of a choral program for middle-aged and older individuals. We integrated our study with qualitative observations of the atmosphere and flow state experienced by the choristers. The data were collected before and after 12 weeks of training, with 23 participants took part in the study. They experienced significant improvements in weight, oxygen saturation, heart rate, and satisfaction of psychological needs. A beneficial trend, although not statistically significant, were observed for blood pressure, cholesterol, triglycerides, stress, psychological needs, and mental health. The observations progressively revealed a more cohesive and focused group. Our findings support the potential for cross-disciplinary collaboration between healthcare and arts policy to promote and enhance health and well-being throughout the lifespan.